2020
DOI: 10.15407/ubj92.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Selected 5-amino-1-aryl-1H-1,2,3-triazole scaffolds as promising antiproliferative agents

Abstract: Development of new effective drugs with low side effects and definite chemical characteristics needs identification of bioactive scaffolds for further structural optimization. New synthesized derivatives of 4-hetaryl-5-amino-1-aryl-1H-1,2,3-triazoles and 3H-[1,2,3]triazolo[4,5-b]pyridines were tested for anticancer activity using 60 human tumor cell lines within 9 cancer types. The selective influence of (5-amino-1H-1,2,3-triazol-4-yl)quinazolin-4(3H)-ones: 2-(5-amino-1-(4-chlorophenyl)-1H-1,2,3-triazol-4-yl)q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In our previous studies, new active compounds with a 1,2,3triazolyl-4-carboxamide motif were reported (Shyyka et al, 2019;Pokhodylo, Shyyka, Finiuk & Stoika, 2020;Pokhodylo, Slyvka & Pavlyuk, 2020). Additionally, 1,2,3-triazolyl-4carboxamide derivatives were found to be inhibitors of the Wnt/-catenin signalling pathway (Obianom et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 96%
“…In our previous studies, new active compounds with a 1,2,3triazolyl-4-carboxamide motif were reported (Shyyka et al, 2019;Pokhodylo, Shyyka, Finiuk & Stoika, 2020;Pokhodylo, Slyvka & Pavlyuk, 2020). Additionally, 1,2,3-triazolyl-4carboxamide derivatives were found to be inhibitors of the Wnt/-catenin signalling pathway (Obianom et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 96%
“…[86] 5-Amino-1H-1,2,3-triazol-4-yl)quinazolin- such as thiazole and oxadiazole led to decreased activity. [87] Maleimide-linked 1,2,3-triazole hybrid 93 showed high cytotoxicity,…”
Section: 23-triazole Linked To Other Heterocyclic Pharmacophoresmentioning
confidence: 99%
“…The ethyl 1-phenyl-5-(pyridin-3-yl)-1H-1,2,3-triazole-4-carboxylate, which inhibited the growth of these cells by 30 % (GP = 70.94 %), demonstrated similar growth value. In general, this NCI-H522 cell line was the most sensitive to such molecular scaffolds (10)(11)(12)(13)(14)17) and the average growth was 75.52 %, the percent of growth was from 68.09 to 86.18 %. Noteworthy, several compounds 10-13, 17 inhibited the thiazol-2-yl)-1H-1,2,3-triazole-4-carboxylic acid 24 showed a significant inhibitory effect on the LOX IMVI (Melanoma) cells (GP = = 44.78 % and 62.25 %, respectively).…”
Section: Evaluation Of Antiproliferative Activity In Vitromentioning
confidence: 90%
“…In our previous work, we found 5-amino-1H-1,2,3-triazole-4-carboxamides as potent antiproliferative agents toward the CNS cancer SNB-75 cell line [8]. The related condensed [1,2,3] triazolo [1,5-a]pyrimidines were also studied and the compounds with cytotoxic activity were found [9,10]. The 5-(trifluo romethyl)-1H-1,2,3-triazole-4-carboxamides were discovered as c-Met-targeting and apoptosis-inducing agents for various tumour cell lines (MCF-7, HepG2, A549, H460, HT-29, MKN-45 and U87MG) with a 3-5-fold higher activity than the positive control drug foretinib [11,12].…”
Section: Introductionmentioning
confidence: 99%